2022
DOI: 10.1002/ardp.202200060
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effect of silymarin nanoemulsion on 5‐fluorouracil‐induced cardiotoxicity in rats

Abstract: 5-Fluorouracil (5-FU)-associated cardiotoxicity has been ranked as the second most common cause of cardiotoxicity induced by chemotherapeutic drugs after anthracyclines. In the present study, we investigated the protective impacts of silymarin (SIL) and silymarin nanoemulsion (SLN) against cardiotoxicity caused by 5-FU in rats. Thirty male Wistar rats were divided into six groups as follows: control, SLN (5 mg/kg), SIL (5 mg/kg), 5-FU + SLN, 5-FU + SIL, and 5-FU. Cardiotoxicity was induced by a single intraper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
(99 reference statements)
0
4
0
Order By: Relevance
“…The same volume of saline (0.9% NaCl) as the solvent was administered IP to the HG (n=6) and FUG (n=6) groups. One hour after administering ATP and solvent, 5-FU 100 mg/kg was injected IP to the animals in the AFU and FUG groups (Safarpour et al, 2022). ATP was administered to the animals once a day for 10 days.…”
Section: Methodsmentioning
confidence: 99%
“…The same volume of saline (0.9% NaCl) as the solvent was administered IP to the HG (n=6) and FUG (n=6) groups. One hour after administering ATP and solvent, 5-FU 100 mg/kg was injected IP to the animals in the AFU and FUG groups (Safarpour et al, 2022). ATP was administered to the animals once a day for 10 days.…”
Section: Methodsmentioning
confidence: 99%
“…The combination of the two can reduce cardiac abnormalities and damage by reducing oxidative stress in cardiomyocytes, increasing the total antioxidant capacity of the heart, and reducing cardiotoxicity caused by 5-fluorouracil treatment [ 130 ]. In addition to these compounds, several studies have found that quercetin, silymarin, asiatic acid, tanshinone IIA, and many other compounds can have some protective effects in the presence of cardiotoxicity from chemotherapy [ 131 , 132 , 133 , 134 , 135 ]. The curcumin mentioned in the previous part of the article also inhibited doxorubicin-induced cardiomyocyte scorching, but this result is controversial [ 136 ].…”
Section: Natural Compounds That Attenuate Adverse Effects Of Chemothe...mentioning
confidence: 99%
“…Since the cardioprotective effect of silymarin was tested mainly in chemotherapeutic drug-induced [ 15 , 16 , 17 ] or ischemia-induced [ 18 ] cardiotoxicity, the aim of this study was to evaluate the cardioprotective effect of silymarin in paracetamol-induced oxidative stress in mice. The hepatoprotective effect was studied as well.…”
Section: Introductionmentioning
confidence: 99%